Perspective: Water-Filtered Infrared-A-Radiation (wIRA) – Novel Treatment Options for Chlamydial Infections? - Kuratli, Jasmin; Borel, Nicole (Frontiers in Microbiology, 2019)
wIRA is a promising therapeutic method, which is particularly used as supportive treatment for wound closure and wound infection treatment and prevention. High penetration properties and its beneficial effects on wound healing processes predispose wIRA irradiation to be a non-invasive treatment method for bacterial infections in tissues. Since C. trachomatis still represents the leading cause of infectious blindness in third world countries (WHO) and wIRA displays beneficial effects on chlamydial infections in vitro without inducing cellular damage in ex vivo eye models and also shows beneficial effects on wound healing, this irradiation technique might represent a promising future treatment for trachoma patients. To this end, further studies investigating shorter irradiation times or irradiation of Chlamydia in chronic infections (the chlamydial stress response (Bavoil, 2014) as well as safety studies in animal models should clearly be performed.